Tapping the Liabilities' Side – Austrian Evidence for Private Equity Investor Involvement, Growth and The Internationalisation of Firms - Jakob Müllner (Asian Academy of Management Journal of Accounting and Finance, 2011)
This paper aims to close one of the most persistent gaps in international business (IB) and strategic management (SM) research by advocating a systematic extension of our research perspective to a more finance-based "liabilities approach". As such, it responds to the recent work of prominent scholars such as Agmon (2006) and Bowe et al. (2010). We challenge the prevailing "finance follows" mindset and - using Private Equity (PE) investors as an illustrative example - we demonstrate how an integrated approach may improve existing theories and open up entirely new avenues of research. We present confirmatory as well as exploratory findings on the impact of investors, suggesting that a company's ownership not only determines a company's financial strength but also has a number of less obvious implications for growth and internationalisation. Our findings suggest that investors may be a strategic asset and can serve as catalysts for a company's growth at several levels of involvement.